Impact of bevacizumab on clinical outcomes and its comparison with standard chemotherapy in metastatic colorectal cancer patients: a systematic review and meta-analysis - Tehnia Naz; Anees ur Rehman; Aleena Shahzad; Muhammad Fawad Rasool; Zikria Saleem; Rabia Hussain (Journal of Pharmaceutical Policy and Practice, 2024)
Background Advances in targeted therapies have expanded the treatment options for colorectal cancer (CRC), allowing for more tailored and effective approaches to managing the disease. In targeted therapy, Bevacizumab is a commonly prescribed anti-VEGF monoclonal antibody that has a direct anti-vascular impact in cancer patients. Vascular Endothelial Growth Factors (VEGFs), especially VEGF-A, are significant agents in promoting tumour angiogenesis.Objective To assess the impact of adding Bevacizumab to chemotherapy on progression-free survival (PFS) and overall survival (OS) in patients with metastatic colorectal cancer.Methodology Comprehensive searches have been performed on electronic databases such as PubMed, and Google Scholar using the following terms: colorectal cancer, adenocarcinoma, Bevacizumab, chemotherapy, and monoclonal antibody.Results In the meta-analysis, 16 out of the 24 included studies were analysed. In the final analysis, incorporating Bevacizumab with chеmothеrapy demonstrated favourable outcomes for OS with a hazard ratio (HR = 0.689,95%CI: 0.51–0.83, I² = 39%, p <0.01) and for PFS with a hazard ratio (HR = 0.77 95% CI: 0.60–0.96, I² = 54%, p < 0.01). The subgroup analysis of PFS, categorised by study dеsign (prospеctivе vs rеtrospеctivе), reveals that the Hazard Ratio (HR = 0.82, 95% CI: 0.62–0.97, I² = 21%, p < 0.01) and for OS with a hazard ratio (HR = 0.73, 95% CI: 0.52–0.86, I² = 17%, p < 0.01).Conclusion Our findings indicate that combining Bevacizumab with chemotherapy enhances clinical outcomes and results in a significant increase in PFS and OS in patients with metastatic colorectal cancer. Positive outcomes are demonstrated by a substantial 23% increase in PFS and 31% increase in OS in patients with metastatic colorectal cancer who undergo Bevacizumab in conjunction with chemotherapy.